2007
DOI: 10.17305/bjbms.2007.3031
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Combination Lisinopril Plus Hydrochlorothiazide in the Treatment of Essential Arterial Hypertension: An Opened, Multi-Centre, Prospective Clinical Trial

Abstract: The aim of this trial was to examine the efficacy and safety of antihypertensive fixed combination lisinopril plus hydrochlorothiazide (Lopril H, Bosnalijek dd) in the treatment of essential arterial hypertension. In our trial we included 297 patients, aged 54.65+/-9.6 years, with treated or untreated hypertension and with high risk of cardiac events, in an opened trial of therapy based on lisinopril plus hydrochlorothiazide. Upon the examination by physicians, patients were divided into three groups in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
2
4
0
1
Order By: Relevance
“…The study demonstrated that patients taking lisinopril/hydrochlorothiazide FDC tablets had a greater reduction in both diastolic and systolic blood pressure, 27 and was safe and effective in most patients, improving their quality of life, 14 which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The study demonstrated that patients taking lisinopril/hydrochlorothiazide FDC tablets had a greater reduction in both diastolic and systolic blood pressure, 27 and was safe and effective in most patients, improving their quality of life, 14 which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…The combination of drugs is a widely used treatment option for hypertension, 5,17 offering not only effective blood pressure control and improved patient compliance, 6 but also protection against cardiovascular disease. 9,12,14 Lisinopril/hydrochlorothiazide is one of the commonly prescribed FDC tablets for first-line therapy in patients with Grade 2 hypertension, comorbidities, and with cardiovascular risk factors. 9,13,17,18 In this study, we compared the bioequivalence of FDC tablets of lisinopril and hydrochlorothiazide in a 10:12.5 ratio (test and reference) in the fasting and postprandial states based on the PK characteristics of 96 subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Несмотря на то, что свободная комбинация лекарственных средств позволяет более точно подобрать дозировки, ее потенциальными недостатками могут явиться нежелание больного принимать «несколько таблеток» и более высокая стоимость по сравнению с фиксированной комбинацией [18]. Gerc V. et al [19] изучали эффективность и безопасность фиксированной комбинации лизиноприла (20 мг) и гидрохлортиазида (12,5 мг). В исследовании приняли участие 297 больных АГ в возрасте 54,7±9,6 лет.…”
Section: преимущества фиксированных комбинаций ингибитора апф и диуре...unclassified